CHARACTERISTIC OF INFESTATION FIRST PERMANENT MOLARS BY CARIES DEPENDING ON TEETH ODONTOGLIFIK IN CHILDREN OF POLTAVA - Каськова, Л.Ф.; Солошенко, Ю.І.; Амосова, Л.І.; Бережна, О.Е.; Хміль, О.В. (World of Medicine and Biology, 2014)
The study found that the first permanent molars of the lower jaw most often affected by caries in the first two years of observation. During the 3rd year study showed a trend towards reduction in the intensity lesion molars. The frequency of lesions of the lower molars, which were more complex structure of chewing surfaces (type Y5 and +5) was significantly higher than the molar occlusal surface of type +4. Since children's first permanent molars of the lower jaw are complicated structure of chewing surface, and the intensity of caries lesions is highest in the first 2 years after the eruption, they need preventive measures in the early periods.
Keywords: children; odontoglifica; molars; tooth decay